Tinjauan Yuridis terhadap Pelaku Tindak Pidana Pembunuhan Bayi (Studi Kasus Putusan Nomor 1123/Pid.Sus/2018/Pn Dps) - Desak Ketut Parwati; I Wayan Rideng; Ni Made Sukaryati Karma (Jurnal Konstruksi Hukum, 2021)
Protection for babies has started since in the womb. In accordance with article 2 Burgerlijk Wetboek that a child who is still in his mother's womb is considered a legal subject as long as the interests of the child are desired. However, nowadays cases of infanticide often occur, so in this case legal protection is needed. The purpose of this research is to analyze the regulation of criminal sanctions for the perpetrators of the crime of infanticide and the judge's consideration of the perpetrators of the crime of infanticide. The type of research used in this paper is a normative law research type with a statutory and conceptual approach. The sources of legal materials used are primary and secondary legal materials. After the data is collected, then the data is analyzed systematically. The results of the research reveal that the setting of sanctions for perpetrators of the crime of infanticide is as regulated in Law Number 35 of 2014 concerning Child Protection. The judge's considerations in making a decision against the perpetrators of the crime of infanticide which resulted in death, include; witness statements that have been submitted by the public prosecutor before the trial, based on the testimony of the defendant at the trial and based on the elements of the crime charged by the public prosecutor in the single indictment have been fulfilled.